2019
DOI: 10.1002/aur.2069
|View full text |Cite
|
Sign up to set email alerts
|

Inferring power and dominance from dyadic nonverbal interactions in autism spectrum disorder

Abstract: Research studies to date have revealed conflicting results with respect to the processing of nonverbal cues from social interactions in autism spectrum disorder (ASD). Therefore, the aim of the present study was to investigate the contribution of two important factors for the perception of dyadic social interactions, namely (a) the movement contingency and (b) the spatial context. To this end, 26 adult participants with ASD and 26 age‐, sex‐, and IQ‐matched typically developed control participants observed ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
0
7
0
1
Order By: Relevance
“…A study's sample size is halved given that all participants are studied in pairs and the unit of analysis is the dyad rather than the individual. While the sample size in the current study may seem small, it is comparable to or even higher than other sample sizes in both autism research [107,108] and IPS research [34,71,[109][110][111]. Nevertheless, it is important to note that, in order to compare between groups with sufficient power and to investigate associations with other variables more extensively, the present results would need to be replicated with a larger sample.…”
Section: Sample Limitationsmentioning
confidence: 68%
See 1 more Smart Citation
“…A study's sample size is halved given that all participants are studied in pairs and the unit of analysis is the dyad rather than the individual. While the sample size in the current study may seem small, it is comparable to or even higher than other sample sizes in both autism research [107,108] and IPS research [34,71,[109][110][111]. Nevertheless, it is important to note that, in order to compare between groups with sufficient power and to investigate associations with other variables more extensively, the present results would need to be replicated with a larger sample.…”
Section: Sample Limitationsmentioning
confidence: 68%
“…These authors find that, on an explicit verbal task of recounting a story in a diffusion chain of 8 individuals, ASD and typical groups were equally good at retaining the details of the story, whereas the MIXED group showed a steeper decline in detail retention. It is therefore important to highlight, given the difficulties of individuals with ASD with implicit but not explicit processing [107] that there may be differences in terms of coordination ability in ASD, depending on the domain of investigation.…”
Section: Dyads With Autistic Participants Show Reduced Ipsmentioning
confidence: 99%
“…Even though ''awkwardness'' in social situations, struggling to recognize social rank in society are considered core symptoms of ASD, there is very limited scientific literature covering the topic of social dominance in ASD. However, a recent study shows that subjects living with ASD tend to judge dominance in a social interaction slower, indicating malfunctioning nonverbal processing (Kuschefski et al, 2019). There are some other indirect examples which stem from dysfunctional social hierarchy recognition in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…The study of social dominance in ASD patients is still limited, and a few studies have suggested an atypical way of recognition in these patients when they were asked to judge who is dominant between two persons presented as schematic diagrams or animations [31,32]. Further, a series of studies reported dominant social phenotypes in multiple rodent models associated with ASD [33][34][35].…”
Section: Discussionmentioning
confidence: 99%